2017
DOI: 10.1016/j.neuro.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and oxidative stress-related effects associated with neurotoxicity are maintained after exclusively prenatal trichloroethylene exposure

Abstract: Trichloroethylene (TCE) is a widespread environmental toxicant with immunotoxic and neurotoxic potential. Previous studies have shown that continuous developmental exposure to TCE encompassing gestation and early life as well as postnatal only exposure in the drinking water of MRL+/+ mice promoted CD4+ T cell immunotoxicity, glutathione depletion and oxidative stress in the cerebellum, as well increased locomotor activity in male offspring. The purpose of this study was to characterize the effects of exclusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 71 publications
(70 reference statements)
1
22
0
Order By: Relevance
“…The course of treatment and the quality of patients' life have been greatly affected. 22) In recent years, researchers have attached more and more importance to oxidative stress because of its role in the delayed-and accumulated-type of neurotoxicity. 23) Mammalian nerves are known to be more susceptible to oxidative stress because of their high content of phospholipids, mitochondria rich axoplasm and also due to weak cellular antioxidant defence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The course of treatment and the quality of patients' life have been greatly affected. 22) In recent years, researchers have attached more and more importance to oxidative stress because of its role in the delayed-and accumulated-type of neurotoxicity. 23) Mammalian nerves are known to be more susceptible to oxidative stress because of their high content of phospholipids, mitochondria rich axoplasm and also due to weak cellular antioxidant defence.…”
Section: Discussionmentioning
confidence: 99%
“…22) In recent years, researchers have attached more and more importance to oxidative stress because of its role in the delayed-and accumulated-type of neurotoxicity. 23) Mammalian nerves are known to be more susceptible to oxidative stress because of their high content of phospholipids, mitochondria rich axoplasm and also due to weak cellular antioxidant defence. 24) In addition, lacking of blood-brain-barrier makes peripheral nervous system more susceptible to the injury of chemotherapeutic accumulation like oxaliplatin, increasing the level of reactive oxygen species (ROS) and destroying the antioxidant-related proteins, and results in the disorder of redox balance in the end.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence to suggest that TCE promotes immune-mediated inflammatory diseases, hypersensitivity and autoimmunity in humans (Cooper et al, 2009;Dai et al, 2015;EPA, 2011;Huang et al, 2015;Khader, Gaffen, & Kolls, 2009;Parks & De Roos, 2014;Zhao et al, 2016). We and others have shown the effect of continuous developmental exposure to TCE in mice encompassing gestation, lactation, and early life generated CD4 + T-cell alterations and/or early signs of tissue inflammation in both normal and autoimmune-susceptible mouse strains (Blossom, Melnyk, Li, Wessinger, & Cooney, 2017;Gilbert, Woodruff, & Blossom, 2014;Peden-Adams et al, 2006;Peden-Adams et al, 2008).…”
Section: Introductionmentioning
confidence: 86%
“…There is also evidence to suggest that TCE promotes immune‐mediated inflammatory diseases, hypersensitivity and autoimmunity in humans (Cooper et al, ; Dai et al, ; EPA, ; Huang et al, ; Khader, Gaffen, & Kolls, ; Parks & De Roos, ; Zhao et al, ). We and others have shown the effect of continuous developmental exposure to TCE in mice encompassing gestation, lactation, and early life generated CD4 + T‐cell alterations and/or early signs of tissue inflammation in both normal and autoimmune‐susceptible mouse strains (Blossom, Melnyk, Li, Wessinger, & Cooney, ; Gilbert, Woodruff, & Blossom, ; Peden‐Adams et al, ; Peden‐Adams et al, ). We recently reported that continuous developmental exposure to TCE beginning at gestation generated autoimmune hepatitis (AIH)‐like tissue pathology at postnatal day (PND) 259 even when TCE was removed from the drinking water at PND154 (Gilbert, Bai, Barnette, & Blossom, ).…”
Section: Introductionmentioning
confidence: 91%
“…We and others have shown that continuous developmental exposure to TCE in mice (gestation, lactation, and early life) generated CD4 + Tcell alterations and/or early signs of tissue inflammation in both normal and autoimmune-susceptible mouse strains [58,59]. Similar immune-altering effects were observed with gestation- or postnatal-only exposure in young adult mice [60,61]. We recently reported continuous chronic exposure to low-level TCE beginning at gestation generated autoimmune hepatitis at postnatal day 259 even when TCE exposure was stopped 15 weeks earlier [62].…”
Section: Trichloroethylenementioning
confidence: 64%